Bimetallic metal organic framework anchored multi-layer black phosphorous nanosheets with enhanced electrochemical activity for paracetamol detection. (20th June 2023) - Shalauddin, Md.; Akhter, Shamima; Basirun, Wan Jeffrey; Lee, Vannajan Sanghiran; Marlinda, Ab Rahman; Ahmed, Syed Rahin; Rajabzadeh, Amin Reza; Srinivasan, Seshasai
Highlights: Nanohybrid of Iron-magnesium MOF and black phosphorus nanosheets have been reported. A biomolecule-free electrochemical paracetamol sensing strategy have been developed. Nanohybrid was highly specific to the target in the presence of interfering compounds. A detection limit of 0.0007 µM and sensitivity of 23.87 µA µM −1 cm −2 was achieved. ABSTRACT: Biorecognition free electrochemical sensors offer a simple and field-applicable analyte detection system for diverse applications. Moreover, the integration of nanostructured materials on the sensing system could amplify the electric signal and enhance the sensitivity of the detection. In this study, a biomolecule-free electrochemical paracetamol sensing strategy using bimetallic iron-magnesium metal-organic frameworks (Fe-Mg-MOF) and black phosphorus nanosheets (BPN) has been presented. The synthesized Fe-Mg-MOF, BPN and the nanocomposite of Fe-Mg-MOF-BPN have been characterized using field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray electron spectroscopy (XPS), EDX, (Fourier transform infrared spectroscopy) FTIR, (ultraviolet spectroscopy) UV spectroscopy and (X-ray diffraction spectroscopy) XRD. The high thermal stability and high surface area were confirmed by thermogravimetric analysis (TGA) and Brunauer-Emmett-Teller (BET) analysis. The electrochemical study shows a significantly enhanced electric signal of the Fe-Mg-MOF-BPN nanocomposite compared to the Fe-Mg-MOF and BPN. Furthermore, the computational analysis Fe-Mg-MOF-BPN was investigated by Biovia Materials Studio software suite (BIOVIA DISCOVERY STUDIO 2021 which revealed that the Fe-Mg-MOF-BPN nanocomposite has a strong interaction with the target paracetamol compared to Fe-Mg-MOF and BPN. Under optimized conditions, the proposed sensing method shows a linear detection range with two segments of 0.002 – 30 µM and 40 µM to 700 µM for paracetamol with the calculated sensitivity values are 23.61 µA µM −1 cm −2 and 0.94 µA µM −1 cm −2, respectively. The sensor showed a low limit of detection (LOD) of 0.0007 µM which was calculated from the first segment of the linear range. The real-life applicability of the fabricated sensor was examined in pharmaceutical formulations and simulated blood samples. The percentage of recovery of paracetamol in pharmaceutical formulation and simulated blood samples was 99.56% -100.60% and 99.50%-101.75%, respectively. Graphical abstract: Image, graphical abstract